Single Arm Clinical Study to Evaluate the Effect of Nasya in Meniere’s Disease followed by Concomitant Treatments (International Journal of Ayurveda and Pharma Research, 2022)
Meniere’s Disease is an ear disease specifically of inner ear. The clinical presentation includes vertigo which is episodic, sensorineural hearing loss which fluctuates, tinnitus and sensation of fullness of ear (aural fullness). Associated complaints includes headache, nausea, drop attacks (otolith crisis of Tumarkin). Meniere’s disease is relapsing in nature which greatly affects patient’s daily activities. The highest prevalent age group is 30-60 years of age. The main pathology occurs as the result of endolymphatic sac distension caused by excessive production or faulty absorption of endolymph or both. The cause is not known clearly. But few factors may contribute in the pathophysiology of Meniere’s disease like excessive retention of water and sodium, allergic reactions, vasomotor disorders, auto immune disorders like rheumatoid fever, middle ear infections etc. Acharya Sushruta has explained Karnarogas like Karnanaada, Karnakshweda, Badhirya which are nearer to Meniere’s disease when studied along with Bhrama. 22 subjects diagnosed with Meniere’s Disease fulfilling the inclusion criteria were selected for the study. Amapachana was done with Shunthi churna. Nasya with Bhringaraja taila followed by Karnapoorana with Bilva Taila and Sarivadi vati along with Dhanwayasa Kashaya and Satwavajaya chikitsa was given. Patient showed significant results in subjective and objective parameters.